Implementation of Chemistry Practicum at SMA Laboratorium Undiksha Singaraja Year 2016/2017 - Ratmini, Wayan Sri (JPI (Jurnal Pendidikan Indonesia), 2017)
This research aimed to describe and explain the practicum topic or subjects conducted in chemistry learning, the teacher’s way conduct experiment, and the factors affecting ecperiment feasibility in SMA Laboratorium Undiksha Singaraja. This research was a qualitative research. Subjects involved in this research were laboratory documents, chemistry teachers, laboratory assistant, and students. Data collection techniques used were study of document, observation, and interview. Data were analyzed by using descriptive interpretive. The results of this research revealed that (1) the practicum topic or subjects conducted in chemistry learning in class X were implementing only one practicum of the five practicum that should be implemented, in class XI were implementing only five practicum of the fourteen practicum that should be implemented, and in class XII were implementing only five practicum of the eleven practicum that should be implemented; (2) the teacher’s way implementing chemistry practicum at SMA Laboratorium Undiksha Singaraja was by group. (3) factors influencing the implementation of chemistry practicum in SMA Laboratorium Undiksha Singaraja were tools and practicum materials, teachers and students’ rediness, laboratory assistant, learning time, and laboratory space. For the teachers in teaching chemistry is will be expected to not only give priority to the giving of the material only but the activities to be conducted also practicum so that the basic competencies that are available on the syllabus can be accomplished